Estimation of the surface deformation of the slopes of the Turrialba volcano (Costa Rica) after an eruption using Sentinel-1A differential synthetic aperture radar interferometry (SAR) - Martínez-Barbáchano, Rubén (2021)
Differential synthetic aperture radar interferometry (SAR) is a technique known in remote sensing for its applications in the generation of digital terrain models and the monitoring of deformations of the earth’s crust. This technique is based on the phase, a parameter present in SAR images and sensitive to terrain topography. Phase differences are related to elevation changes that occur between two satellite scans over the same space. To obtain topographic information, a digital terrain model is required and thus, phase differences provide information for estimating vertical terrain displacement to an accuracy greater than 1 centimeter. In the present work it was possible to estimate the surface deformation that occurred on the western slope of the crater of the Turrialba volcano after the eruption of August 1, 2020. For this purpose, several images captured by the Sentinel-1A sensor of the European Space Agency were used.